2024
DOI: 10.1038/s41598-023-48248-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of Celastrol in the treatment of rheumatoid arthritis based on systems pharmacology and multi-omics

Liuting Zeng,
Ganpeng Yu,
Kailin Yang
et al.

Abstract: To explore the molecular network mechanism of Celastrol in the treatment of rheumatoid arthritis (RA) based on a novel strategy (integrated systems pharmacology, proteomics, transcriptomics and single-cell transcriptomics). Firstly, the potential targets of Celastrol and RA genes were predicted through the database, and the Celastrol-RA targets were obtained by taking the intersection. Then, transcriptomic data and proteomic data of Celastrol treatment of RA were collected. Subsequently, Celastrol-RA targets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Chinese herb Tripterygium wilfordii Hook. F. has the effects of dispelling dampness, relieving swelling and pain, and resisting inflammation ( Zeng et al, 2024 ). Triptolide and tripterine are the two most active components in the extract of Tripterygium wilfordii Hook.…”
Section: Chinese Herbal Medicine Relieves Mf Through Regulating Ncrnasmentioning
confidence: 99%
“…Chinese herb Tripterygium wilfordii Hook. F. has the effects of dispelling dampness, relieving swelling and pain, and resisting inflammation ( Zeng et al, 2024 ). Triptolide and tripterine are the two most active components in the extract of Tripterygium wilfordii Hook.…”
Section: Chinese Herbal Medicine Relieves Mf Through Regulating Ncrnasmentioning
confidence: 99%
“…Zeng et al 145 reported that post analysis integration of transcriptomics and proteomics data of synovial cells and fibroblasts has been performed to better understand inflammation pathways in which the drug celastrol impacts rheumatic arthritis cells by modulating inflammation, inhibiting chemokine pathways and osteoclast differentiation, and promoting synovial cell apoptosis.…”
Section: Examples Of Omics and Multiomics Studies Focused On Health A...mentioning
confidence: 99%